Pemidanaan terhadap Perbedaan Pemahaman: Analisis Hak Asasi Manusia atas Perkara Penodaan Agama di Indonesia - Moch. Choirul Rizal; Michelle Salma Khotom Aji; Muhamad Atji Firmansyah; Unsa Elen Purwanti (Jurnal HAM, 2025)
The right to have different interpretations of mainstream religious teachings in Indonesia can lead to criminal penalties. In practice, judges often rely on expert testimony to gain confidence that "those who are different" have committed the crime of blasphemy. The research method employed in this article is the Human Rights (HAM) research method, which emphasizes the study of court decisions related to criminal acts of blasphemy in Indonesia, particularly regarding the spread of beliefs that differ from the mainstream as blasphemy. The court decisions are analyzed using a human rights approach, especially the right to freedom of religion or belief (FoRB). As a result, 3 (three) of the 11 (eleven) court decisions reviewed still ignore the principle of impartiality in testing differences in interpretations of mainstream religious teachings. Judges do not open up space for dialogue to explore expert testimony from the defendant's perspective. This criminal justice practice, in turn, will undermine FoRB as a meaningful concept. In the future, differences in interpretation of mainstream religious teachings will not be a matter of criminalization, but rather of dialogue. Even if criminalization is necessary, what is prohibited is the crime of broadcasting religious hatred, the judicial process for which is carried out independently and impartially.